INCREASING DIVERSITY IN NURSING TO REDUCE HEALTH DISPARITIES AND ACHIEVE HEALTH EQUITY - SAFDAR , F; QADIR , S (Biological and Clinical Sciences Research Journal, 2024)
In modern healthcare systems, achieving health equity remains paramount, yet persistent health disparities among diverse populations present significant challenges. The study's main objective is to find the increasing diversity in nursing to reduce health disparities and achieve health equity. This mixed-methods study was conducted in Bahawal Victoria Hospital Bahawalpur from January 2023 till December 2023. The study enrolled a diverse cohort of 550 participants, including registered nurses (RNs), nursing students, nurse educators, and healthcare administrators. Participants were recruited from various healthcare settings, including hospitals, community health centers, and academic institutions. The study included 300 registered nurses (RNs) aged 22 to 65, comprising 75% females and 25% males, demonstrating diverse ethnic representation. Additionally, 150 nursing students aged between 20 and 30 years participated, with 85% females and 15% males, reflecting a diverse demographic composition. Furthermore, 50 nurse educators aged 30 to 55 years were involved, with 60% females and 40% males showcasing diversity. Most participants, comprising 70%, acknowledged that nursing diversity positively impacts patient care and outcomes. However, only 45% felt that their workplace adequately supports diversity initiatives. Regarding healthcare disparities, 60% identified access to care, 50% recognized quality of care, and 45% acknowledged health outcomes disparities as prevalent issues. It is concluded that diversity in nursing holds significant promise for reducing health disparities and advancing health equity. The study's findings underscore the importance of organizational support for diversity initiatives to address systemic barriers in healthcare delivery.